INTRODUCING ETHICAL CODES IN PUBLIC BROADCASTING SERVICES - EXPERIENCE OF BOSNIA AND HERCEGOVINA, MONTENEGRO, CROATIA, MACEDONIA AND SLOVENIA - Nikolić, Mirjana M. (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2017)
Staring from the idea of self-regulation as the most optimal model of democratic and accountable regulation of the media sphere, especially in the field of electronic media, this paper provides a comparative analysis of norms and procedures pertaining to ethical issues in public broadcasting services, in the former Yugoslav republics, now sovereign Balkan states – Slovenia, Croatia, Bosnia and Herzegovina, Montenegro and Macedonia. One of the dilemmas which is discussed is whether the public service institutions should have their own ethical codes that define specific parameters and standards that are appropriate to this media model, or the existence of general codes of ethics is sufficient and applicable to PBS. The paper takes affirmative stance towards the existence of specific ethical codes of public broadcasting services that are in line with the specific social position and responsibility of these media towards the public, since this public is their founder, owner and controller. TV anchors, journalists, producers of commercial, public and civil media have very similar tasks, and are expected to be professional, unbiased, credible, accurate, non-manipulative, ethical, but people who work in public service institutions have a much greater responsibility that should be legislated with special laws and specialized ethical codes.